Approaches to Managerial Control In Interpenetrating Systems: The Case of Government-Industry Relations - Hunt, Raymond G.; Rubin, Ira S. (Academy of Management Journal, 1973)
This paper discusses interorganizational linking mechanisms forming part of the micro-structure of government-industry contracting efforts. It analyzes models of buyer-seller relations under the uncertainties and cross-organizational interactions manifest in research and development. Alternative adaptations of project managerial modes are delineated and a tendency for project management to evolve toward ?shared leadership? forms is posited.